"I grew up on a bike": Cycling and older adults. Issue 1 (March 2015) - Winters, Meghan; Sims-Gould, Joanie; Franke, Thea; McKay, Heather
Abstract A large proportion of the growing population of older adults have low levels of physical activity and face ensuing health and mobility problems. Cycling is a health-promoting and widely accessible transportation option. However, throughout North America cycling rates amongst older adults are extremely low. Evidence from European countries suggests that cycling for older adults is possible and can be a popular travel choice. Therefore, we aimed to assess factors that contribute to cycling trends amongst North American older adults. We used a mixed methods approach to describe cycling behaviors, and facilitators and barriers to cycling in a highly bikeable area of Vancouver, Canada. We conducted a cross-sectional study of older adults (age ≥60 years) who lived in Vancouver's downtown core. During September–October 2012, participants (n=191) recorded travel in 7-day diaries and completed questionnaires on cycling behaviors and perceptions of their neighborhood environments. We conducted in depth interviews with a subset of older adults (n=27) to better understand how they travelled in and around their neighborhoods. Participants demonstrated relatively high levels of cycling; one in four participants reported cycling in a usual week. Cycling mode share was 3.2% (182/5730 reported trips). Notably, this cycling mode share is three times higher than the mode share for older adults living in the region and double the mode share for the general (all-ages) population. Based on a framework analysis of the interviews, factors that facilitate cycling include supportive infrastructure, a history of activity and the social aspects of cycling. Factors that were barriers to cycling, both amongst those who reported cycling and those who did not, focused on safety, including motor vehicle traffic, cyclist behavior and theft. Our results suggest that should favorable policy and environmental conditions exist, cycling as a form of active transportation may be a viable option for older adults.